PROFITABILITY OF COMMERCIAL BROILER CHICKEN UNDER DIFFERENT LIGHT REGIME - B. C. DAS, D. BEHERA; R. SAMANTA S. BERA; N. DEBBARMA (Indian Journal of Animal Production and Management, 2017)
The study was conducted on 200 commercial broiler chickens (Vb-100 strain) understandard managemental conditions to find out the livability and relative economics ofcommercial broiler chicken reared under coloured light, continuous light and intermittent lightregime in deep litter system. After seven days of brooding broiler chicks were divided into 8groups according to different light regime. 100% livability was recorded for all the groupsfrom 2nd to 6th week. Better performance was observed in blue followed by green, red andwhite coloured light. Highest profit was derived from birds kept under blue light (18L+6D)and lowest profit was derived from birds kept under white light (23L+1D).